Topical herbal medicines for atopic eczema: a systematic review of randomized controlled trials. (30th November 2016) - Thandar, Y.; Gray, A.; Botha, J.; Mosam, A.
Summary: Despite the availability of medicines with proven efficacy, many patients use complementary or alternative medicines (CAMs) to manage atopic eczema (AE). Due to the lack of objective information on topical CAMs, this systematic review evaluates the current evidence for the efficacy and safety of topical herbal preparations in AE. Using Cochrane systematic review methodology, PubMed, the Cochrane Library, the Cochrane Central Register of Controlled Trials (CENTRAL), CINAHL (via EBSCO), MEDLINE (via EBSCO), Proquest Health and Medical Complete, GREAT and CAM‐QUEST were searched from inception until June 2014. Bibliographies of retrieved studies were hand searched for further relevant trials. All controlled clinical trials of topical herbal medicines for AE in humans of any age were included regardless of the control intervention or randomization. Only English‐language publications were considered. Eight studies met the inclusion criteria. Seven investigated extracts of single plants and one an extract from multiple plants. Only two studies that showed a positive effect were considered to have a low risk of bias across all domains (those of liquorice gel and Hypericum perforatum ). In these two, the test product was reported to be superior to placebo. Despite variations in diagnostic criteria and lack of validated tools for outcome assessments in one of these, the promising results may warrant continued research in better‐designed studies. No meta‐analysis was performed due to heterogeneity in all studies. There is currently insufficient evidence of efficacy for any topical herbal extract in AE. Many studies had methodological flaws and even those showing efficacy were single trials with small patient cohorts. Abstract : What's already known about this topic? Patients use topical complementary or alternative medicines to manage atopic eczema. Objective evidence of efficacy and safety is lacking and is essential for clinicians and patients to make informed choices. What does this study add? Of six studies that displayed superiority of treatment over placebo, only two studies, of liquorice gel and Hypericum perforatum, were considered to have a low risk of bias across all domains. The promising effect of these two therapies for atopic eczema warrants continued research in well‐designed studies. Linked Comment: Booth. Br J Dermatol 2017; 176 :288 .